Validity, reliability and usefulness of smartphone and kinovea motion analysis software for direct measurement of vertical jump height - Pueo, B.; Penichet-Tomas, A.; Jimenez-Olmedo, J. M. (Physiology & Behavior, 2020)
Jumping is a simple exercise determined by several biomechanical and physiological factors. Measures of vertical jump height are common and easy to administer tests of lower limb muscle power that are carried out with several types of equipment. This study aimed to validate and address the usefulness of the combination of smartphone and computer-based applications (Smartphone-Kinovea) against a laboratory-based Motion Capture System. One hundred and twelve healthy adults performed three maximal-effort countermovement jumps each. Both instruments measured the heights of the 336 trials concurrently while tracking the excursion of the body center of gravity. The vertical velocity at take-off vto and the impulse J were computed with jump height h measures. Intraclass correlation coefficient (ICC) results indicated very high agreement for h and vto (0.985) and almost perfect agreement for J (0.997), and Cronbach's a=0.99. Low mean differences were observed between instruments for h: -0.22 ± 1.15 cm, vto: -0.01 ± 0.04 m/s, and J: -0.56 ± 2.92 Ns, all p<0.01. The smallest worthwhile change (SWC) and the typical error of measurement (SEM) were 1.34 cm, 0.81 cm for h; 1.15 m/s, 0.03 m/s for vto, and 2.93 Ns, 2.25 Ns for J, so the usefulness of the method is established (SWC/SEM>1). Bland-Altman plots showed very low mean systematic bias ± random errors (-0.22 ± 2.25 cm; -0.01 ± 0.08 m/s; -0.56 ± 5.73 Ns), without association between their magnitudes (r2=0.005, r2=0.005, r2=0.001). Finally, very high to practically perfect correlation between isntruments were observed (r = 0.985; r = 0.986; r = 0.997). Our results suggest that the Smartphone-Kinovea method is a valid and reliable, low-cost instrument to monitor changes in jump performance in a healthy, active population diverse in gender and physical condition.